Atlas of soft tissue and bone pathology : with histologic, cytologic, and radiologic correlations - Dodd, Leslie; Bui, Marilyn M. (Demos Medical, 2015)
""; ; This is an abundantly illustrated resource for diagnosis of bone and soft tissue lesionsóa particular challenge due to their rarity and complexity. In addition to carefully selected histologic photographs, this unique atlas enhances standard visual information with illustrations of imaging findings, cytology, and molecular and cytogenetic information. This vivid pictorial survey is arranged in a pattern-oriented approach based on the actual working method used in daily practice. ; The authors are expert educators in surgical and cytopathology and experienced diagnosticians in the compl.